Tratamento contábil e tributário de receitas em empresas do setor musical - Segura, Leni Regina (2018)
Scope of the Study: The purpose of this applied research is to examine the earnings obtained by small and mid-size companies in the musical industry, formed by established musicians who are the members thereof, in order to identify: (i) if such earnings are being duly posted in their accounting records and taxed accordingly, (ii) if it is possible to apply the "CPC 47' [Accounting Regulation] to such earnings; and, (iii) if such earnings obtained by the musical companies are, in whole or in part, contemplated by the tax immunity provided in Art. 150, VI, item “e” of the Brazilian Constitution. Design/Method/Approach: This research has an exploratory character with a qualitative approach. The accounting and tax data have been obtained from four (4) small and mid-size companies of the musical industry, selected among the clients of the author's accounting firm. Results: The main results indicate that the companies of the musical industry do not record their earnings taking into consideration the essence of the contracts entered into with third parties, do not segregate their earnings by the particularities of each object developed and apply the immunity provided in Art. 150, VI, item “e” to the earnings not contemplated by such constitutional immunity. Practical Implications: The correct record keeping of such earnings implies: i) reliable financial statements; and ii) reduction of tax risks. Originality and Contributions: The originality of this applied research consists in studying companies in the music industry in order to properly classify their earnings based on the "CPC 47", and thus apply thereto the correct accounting and tax treatment.